Determinants of suboptimal complementary feeding practices among children aged 6–24 months in Natuna: A Case-control study - Effatul Afifah; Arif Sabta Aji; AD Nabiella; Yhona Paratmanitya; Herni Dwi Herawati; Herwinda Kusuma Rahayu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Stunting affects more than 22% of children under five years of age globally, including approximately 6.3 million in Indonesia. The 2024 SSGI reported a decline in the national prevalence of stunting from 21.5% to 19.8% in 2023, surpassing the 20.1% target, with a further reduction goal of 14.2% by 2029. However, Natuna Regency reported a prevalence of 16.1% in 2023, exceeding the national target and highlighting the need for evidence-based intervention. This study aimed to investigate the association between maternal knowledge, attitudes, involvement, and self-confidence in complementary feeding practices among stunted children aged 6–24 months. This study employed a case–control design involving 122 mothers (60 cases and 62 controls). The study was conducted in the working areas of Puskesmas Serasan and Puskesmas Serasan Timur from September to November 2024. Data were collected using structured questionnaires and analyzed using chi-square tests and logistic regression. Most case group mothers had low knowledge (21.3%), unfavorable attitudes (48.4%), limited involvement (42.6%), and low self-confidence (50%). The results also showed significant associations between maternal factors and feeding practices (p ≤ 0.001). Poor knowledge was the strongest predictor of stunting (OR = 24.0), followed by low self-confidence (OR = 8.8), negative attitude (OR = 7.29), and limited involvement (OR = 5.6). Strengthening maternal capacity is essential for improving feeding practices.